Non-adherence to lifestyle modifications (Diet and exercise) amongst type 2 diabetes mellitus patients attending extension II clinics in Gaborone, Botswana - Bisiriyu, Ganiyu Adewale (University of Limpopo (Medunsa Campus), 2010)
Abundant literature supports the beneficial effects of diet and exercise recommendations for improving and maintaining glycaemic levels of people with type 2 diabetes mellitus. Patient adherence to therapeutic lifestyle measures is notoriously difficult to initiate and sustain; however, reason for non-adherence amongst diabetes population is very complex and multi-faceted in nature. Objectives To determine rates of non-adherence and reasons/barriers for not adhering to diet and exercise recommendations amongst type 2 diabetes mellitus patients attending Extension II clinic in Gaborone, Botswana. Summary of methods Design: descriptive cross-sectional study using self administered questionnaire Setting: Extension II clinic, a public family practice in Gaborone, Botswana. Study population: Consenting adults diagnosed with type 2 diabetes mellitus, aged 30 years or older, diagnosed 2 or more years and on clinic care. Sample selection: Convenience sampling method was used to select 35 subjects per month, over a period of three successive months and a total of 105 participants were recruited into the study, made up of 44 men and 61 women. Results 104 correctly filled questionnaires were included in the data analysis, of which, 59% were female. Estimated rates of non-adherence to diet and exercise were 37.4%; 95% CI, 27.7 – 46.3% and 52%; 95% CI, 42.4 – 61.6% respectively. The main perceived reasons for non-adherence to diet were granting self-permission (36.5%), lack of information (33.3%), eating out (31.7%), financial constraints (28.8%) and poor self control (26.9%); while the main perceived reasons for non-adherence to exercise were lack of information (65.7%), exercise as potentially exacerbating illness (57.6%), lack of exercise partner (24.0%), specific locations away from home (18.0%), and winter weather (15.4%). The overall reasons for not adhering to diet and exercise include lack of moral and emotional supports from the spouse (54.1%), family members (44.8%), and friends (58.7%). 95% and 67.3% of the participants had reported that diet and exercise respectively could improved and maintained their diabetic control. Conclusion Non-adherence to diet and exercise recommendations amongst type 2 diabetes patients is far more prevalent and no particular single reason could be attributed to poor adherence to either diet or exercise recommendations, rather a combination of many factors.
Thesis (M Med (Family Medicine))--University of Limpopo (Medunsa Campus), 2010.
Keywords: Diet and exercise; Diabetes millitus